Depression in Patients with Epilepsy in Nigeria: Phenomenology and Predictors - Ogundare, Temitope (International Journal of Epilepsy, 2021)
Objectives In this article, we aimed to determine the correlates of depression among patients with epilepsy in Neuropsychiatric Hospital, Aro, Abeokuta, Nigeria.Methods 270 patients with epilepsy attending the outpatient clinic of the hospital were recruited and assessed using sociodemographic questionnaire, MINI-Plus, and BDI-II.Results The mean (standard deviation [SD]) age of the respondents was 32 (9.9) years, 45.6% were females, and 38.5% were married. Thirty-two (11.9%) patients had a diagnosis of major depressive disorder (MDD) and 13 (4.8%) had a diagnosis of dysthymia. The most common depressive symptoms were loss of pleasure (84.4%), crying (84.4%), self-dislike (81.3%), and loss of energy, tiredness/fatigue, indecisiveness and punishment feelings (78.1% each). Vegetative symptoms such as changes in appetite and sleep and loss of interest in sex were the least common depressive symptoms. In the logistic regression, seizure frequency was the single predictor of MDD and dysthymia. Patients who had at least one seizure per week were five times more likely to develop MDD (OR = 5.1, p = 0.014) and 16 times likely to have dysthymia (OR= 16.0, p = 0.0007). Patients who had at least one seizure per month were 3 times more likely to develop MDD (OR = 3.3, p = 0.029).Conclusion Seizure frequency is an independent predictor of depression among patients with epilepsy. Patients with poor seizure control are at higher risk of developing depression and should be routinely screened for depression.
Keywords: epilepsy; major depressive disorder; Nigeria; dysthymia; depression